To solve the equation \(-3 - |6 - 3x| + 7 = 4\), we can first simplify it:
\[ -3 + 7 - |6 - 3x| = 4 \]
\[ 4 - |6 - 3x| = 4 \]
Now, we can isolate the absolute value:
\[ -|6 - 3x| = 4 - 4 \]
\[ -|6 - 3x| = 0 \]
This implies:
\[ |6 - 3x| = 0 \]
The absolute value of a number is zero only when the number itself is zero. So, we can write:
\[ 6 - 3x = 0 \]
Now, we can solve for \(x\):
\[ 3x = 6 \]
\[ x = 2 \]
Now we can verify if this value of \(x\) satisfies the original equation:
Substituting \(x = 2\):
\[ -3 - |6 - 3(2)| + 7 = 4 \]
Calculating the absolute value:
\[ 6 - 3(2) = 6 - 6 = 0 \]
So:
\[ -3 - |0| + 7 = -3 + 0 + 7 = 4 \]
The left side equals the right side, confirming that our solution is correct.
Thus, the solution is:
\[ \boxed{2} \]